Subcutaneous EEG Monitoring Reveals AED Response and Breakthrough Seizures - Sigge Weisdorf; Ivan C. Zibrandtsen; Troels W. Kjaer (Case Reports in Neurological Medicine)
Unrecognized seizures are a common problem in temporal lobe epilepsy potentially leading to undertreatment. Objective seizure counting using EEG home monitoring for prolonged periods with a minimally invasive device has not been feasible until now. We present a case in which a novel, subcutaneous EEG device was utilized to provide an objective seizure count. This information revealed unrecognized breakthrough seizures and informed treatment response, prompting treatment adjustment. The case illustrates how objective seizure counting in epilepsy using new devices can completely change diagnosis and management.